The equation above has two real roots one of which is for integers with square free and positive.
Find .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
We may factor the equation as:
2 0 0 0 x 6 + 1 0 0 x 5 + 1 0 x 3 + x − 2 2 ( 1 0 0 0 x 6 − 1 ) + x ( 1 0 0 x 4 + 1 0 x 2 + 1 ) 2 [ ( 1 0 x 2 ) 3 − 1 ] + x [ ( 1 0 x 2 ) 2 + ( 1 0 x 2 ) + 1 ] 2 ( 1 0 x 2 − 1 ) [ ( 1 0 x 2 ) 2 + ( 1 0 x 2 ) + 1 ] + x [ ( 1 0 x 2 ) 2 + ( 1 0 x 2 ) + 1 ] ( 2 0 x 2 + x − 2 ) ( 1 0 0 x 4 + 1 0 x 2 + 1 ) = 0 = 0 = 0 = 0 = 0
Now 1 0 0 x 4 + 1 0 x 2 + 1 ≥ 1 > 0 for real x . Thus the real roots must be the roots of the equation 2 0 x 2 + x − 2 = 0 . By the quadratic formula the roots of this are:
x = 4 0 − 1 ± 1 2 − 4 ( − 2 ) ( 2 0 ) = 4 0 − 1 ± 1 + 1 6 0 = 4 0 − 1 ± 1 6 1 . Thus r = 4 0 − 1 + 1 6 1 , and so the final answer is − 1 + 1 6 1 + 4 0 = 2 0 0 .